Hunting for galaxies and halos in simulations with VELOCIraptor. (17th June 2019) - Elahi, Pascal J.; Cañas, Rodrigo; Poulton, Rhys J. J.; Tobar, Rodrigo J.; Willis, James S.; Lagos, Claudia del P.; Power, Chris; Robotham, Aaron S. G.
Abstract: We present VELOCIraptor, a massively parallel galaxy/(sub)halo finder that is also capable of robustly identifying tidally disrupted objects and separate stellar halos from galaxies. The code is written in C++11, use the Message Passing Interface (MPI) and OpenMP Application Programming Interface (API) for parallelisation, and includes python tools to read/manipulate the data products produced. We demonstrate the power of the VELOCIraptor (sub)halo finder, showing how it can identify subhalos deep within the host that have negligible density contrasts to their parent halo. We find a subhalo mass-radial distance dependence: large subhalos with mass ratios of ≳10 −2 are more common in the central regions than smaller subhalos, a result of dynamical friction and low tidal mass loss rates. This dependence is completely absent in (sub)halo finders in common use, which generally search for substructure in configuration space, yet is present in codes that track particles belonging to halos as they fall into other halos, such ashbt +. VELOCIraptor largely reproduces the dependence seen without tracking, finding a similar radial dependence tohbt + in well-resolved halos from our limited resolution fiducial simulation.